Pengaruh Teknologi Informasi Dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja Pada PT. Eratex Djaja Probolinggo - Bahri, Saiful; Tumini, Tumini; Rizky Iroe, Daffa (RELASI : JURNAL EKONOMI, 2024)
This study aims to reveal how the influence of the use of information technology and job characteristics on job satisfaction of employees of PT. Eratex Djaja Probolinggo. The type of research used is quantitative research with a causal associative approach. The population of this study were all employees using information technology, including users of server devices, LAN PCs, integrated production systems, utility systems and marketing systems, totaling 54 employees. The technique of determining the number of samples (respondents) through saturated sampling techniques, so that the number of samples is 54 people. Information technology and job characteristics as independent variables and job satisfaction as the dependent variable. Prior to conducting a test to reveal how the effect is, tests are first carried out on all instruments, both validity, reliability and classic assumption tests with test results, all of which meet the requirements with the SPSS tool. This study found that first, there is a significant positive effect of the use of information technology and job characteristics together on employee job satisfaction. Both individually there is a significant positive effect of the use of information technology and job characteristics on employee job satisfaction. The third found that the most influential among these variables is job characteristics.